Children's participation in research on sensitive topics: addressing concerns of decision-makers. Issue 3 (3rd May 2020) - Powell, Mary Ann; Graham, Anne; McArthur, Morag; Moore, Tim; Chalmers, Jenny; Taplin, Stephanie
ABSTRACT: Although there is general agreement about children's engagement in social research, some researchers continue to experience challenges when seeking approval and support for children's participation from a range of adult stakeholders, particularly when the research involves a sensitive topic. These challenges may reflect different perspectives, conflicting interests, needs or expectations. This paper explores factors that influence the decision-making of key stakeholder groups, including Human Research Ethics Committees, parents and organisational representatives. Building on the kind of objective, rational reasoning that underpins much ethical decision-making, the findings, from interviews with 42 participants across stakeholder groups, draw attention to influential issues grounded in perceptions of: the institution and researcher undertaking the research; the project itself; children's characteristics and contexts. Collectively, such issues point to the critically important role of mutually respectful relationships between researchers and stakeholders as the basis for designing and implementing ethical research that gives close attention to stakeholder concerns.